(untitled) (Bangladesh Journal of Psychiatry, 2024)
Body dysmorphic disorder is a chronic disorder involving imagined or partial appearance defects that lead to significant impairment in everyday life. It is quite prevalent but often remains a clinically under diagnosed psychiatric condition. Severe cases of the body dysmorphic disorder were often camouflaged by concurrent diseases like major depressive disorder, obsessive compulsive disorder, substance use disorder and social anxiety disorder. The case presented here was a 17-years-old boy who was previously diagnosed as a case of obsessive-compulsive disorder. The constellation of symptoms prompted evaluation for body dysmorphic disorder and subsequently targeted treatment. This case report highlighted the complexities associated with diagnosing and providing treatment of body dysmorphic disorder. Bang J Psychiatry 2023;37(1): 23-24